Oral tolerance induction and food allergy prevention: Oral tolerance induction and food allergy prevention - Tsikhan, Natallia; Belevtsev, Mikhail (Journal of Medical Science, 2019)
This review aims to provide an overview of the issue of oral tolerance induction in early childhood and allergy manifestation. We discuss changes in epidemiology of allergic diseases that have occurred over the last decades in the context of current knowledge about environmental factors affecting prevalence of these diseases. Also this article presents current data about causes of "hygiene hypothesis" expansion to "microflora hypothesis" as well as an immunological background of this process; describes how immune factors of cord blood and breast milk, maternal and infant’s elimination diet, timing a solid food intake impact on immune system development and tolerance induction in early childhood. Current knowledge on issues of tolerance induction and allergy should induce update of allergy prevention recommendations in the nearest future.
Keywords: immune factors; cord blood; breast milk; microbiota; elimination diet